The Effect of Overeducation on Unemployment Duration in Indonesian - Maya Friska; Arie Damayanti (Jurnal Ekonomi Dan Statistik Indonesia, 2021)
Unemployment has a negative impact on individuals. During the unemployment period, job seekers will use their money or assets savings and as long as the unemployment period is not over, the job seekers will need more money or assets in order to meet their needs during the unemployment period. The open unemployment rate (TPT) in Indonesia is more dominated by people with high school education and above indicating an oversupply of graduates with high education. This oversupply is one of the causes of the mismatch in the level of education or also referred to as overeducation. This study aims to determine the effect of overeducation on unemployment duration in Indonesia. This study uses the National Labor Force Survey Panel (SAKERNAS PANEL 2017) through a survival analysis approach with Cox Proportional Hazard Regression. The results showed that overeducation would extend the length of time someone was looking for work.